Concept of Retribution and Blood Money in Islam and Judaism: Similarities and Differences - Nawaz, Saleem; Shaikh, Muhammad Ali (Journal of Islamic and Religious Studies, 2022)
In all Divine religions, the law of retribution was legislated to protect the sanctity and survival of human life, to end crimes and oppression, prevention of chaos and anarchy, and to maintain collective order and peace in the society. In this regard, an analytical and comparative study of the concept of retribution in Islam and Judaism, the types of retribution, the retribution of injuries and damaged limbs, the principles of testimony, the procedure for issuing and implementing punishment and authority of implementation of punishments, has been done in the light of the Old Testament, the Holy Qur'ān and the Aḥādīth. The study concludes that in Judaism, the law of retribution is required in both cases, i.e; intentional murder and unintentional murder and forgiving the murderer and taking blood money is strictly forbidden, while in Islam, the law of retribution is only for intentional murder and the heirs is obliged to take Qiṣāṣ or to take blood money or to forgive the murderer, while in unintentional murder, the heirs can either take blood money or forgive the murderer. In Islam, only government is authorized to execute the retribution, while in Judaism, the heirs of the deceased can also kill the murderer. In both religions, the testimony of more than one person is necessary for the execution of Qiṣāṣ.